Graph representation for two-dimensional scene understanding by the cognitive vision module. (23rd December 2016) - Bielecki, Andrzej; Śmigielski, Piotr
In this article, the cognitive vision module of an autonomous flying robot is studied. The problem of the scene understanding by the robot, which flies on the high altitude, is analyzed. In such conditions, the examined scene can be regarded as two-dimensional. It is assumed that the robot operates in the urban-type environment. The scene representation is stored in the neighborhood graph that collects data about the objects locations, shapes, and their spatial relations. The fragments of the scene are understood by the robot in the context of neighborhoods of the objects. It is shown that such information can be effectively used for recognition of the object, while many objects of similar shape exist in the scene. In the proposed recognition process, not only the information about the shape of the object is utilized but also the spatial relations with other objects in its close neighborhood are examined.